The use of digital educational resources and the teaching of the additive field: a systematic literature review (Research, Society and Development, 2021)
This article aims to carry out a Systematic Literature Review (RSL) of theses and dissertations from the last 10 years that present as a research field the use of Digital Educational Resource (RED), as well as the teaching of concepts aimed at addition and subtraction, or that is, the additive structures. A mixed RSL of qualitative convergence was performed. The search portal for the research was the CAPES Theses and Dissertations Portal, analyzing a total of 9 researches, among the 27 found, as they fit the words used in the search. Given this analysis, it was found that there is a need for the emergence of new research that present the use of RED in teaching the additive field, in view of the need to teach concepts related to the additive field using RED can favor teaching and learning. It is expected that this research will contribute to the dissemination of new research that address the topic discussed.